(3GdYdGbGJ GdGbJUGOjI h GdGLJeGYjI h GdOYGhi h GdJhcjdGJ GdTQYjI h GdbGfhfjI ddeSdejf h GdeSMjjf h ddQYGjG GdYKeGfjjf h GdGLGfH aj GdYgO GdYKeGfj (B/s - (3MdGb, MSGfs ((3HjQhJ(B: s (3efThQGJ GdMdHj GdMbhbjI(B, s, 2009)
(3CKQ ehbY HjQhJ aj JWhQ GdYdGbGJ GdGbJUGOjI h GdGLJeGYjI Hjf GdHjGQJI , OhQ bdYI h CHQGL h ejfGA HjQhJ GdeMQhSI aj JfejI GdYdGbGJ GdGLJeGYjI h GdGbJUGOjI aj HjQhJ , OhQ CShGb h WQb GdehGUdGJ HjQhJ GdYKeGfjI aj JWhQ GdYdGbGJ GdGLJeGYjI h GdGbJUGOjI aj HjQhJ , OhQ hSGFd GdGJUGdGJ h GdMQcI GdJLGQjI aj JWhQ GdYdGbGJ GdGbJUGOjI h GdGLJeGYjI aj HjQhJ , GdedGeM GdGbJUGOjI h GdGLJeGYjI aj HjQhJ aj GdbQf GdJGSY YTQ h CNjQG GdYdGbGJ GdGbJUGOjI h GdGLeGYjI Hjf GdeSdejf h GdeSjMjjf h GdQYGjG GdYKeGfjjf h GdCLGfH aj HjQhJ aj GdbQf GdJGSY YTQ (B.s
(3eQGLY U(B.197 (3; hKGFb U(B.171 (3; NQGFW h LOGhd U(B.189s
Keywords: (3GdYdGbGJ GdELJeGYjIs; (3GdYdGbGJ GdGbJUGOjIs; (3dHfGf(B- (3GdYdGbGJ GdEbJUGOjI hGdELJeGYjIs